Sensitivity to ionising radiation of lymphocytes from Huntington's chorea patients compared to controls. Issue 3 (June 1982) - McGovern, D; Webb, T
Abstract : Blood samples were collected from 22 patients with Huntington's chorea and from 22 matched controls. Lymphocytes were separated from aliquots of each sample and cultures set up both from these and from further aliquots of whole blood. After 24 hours, half of each culture was subjected to X irradiation. Seventy-two hours later the percentages of live lymphocytes were estimated for each half of every culture and the viability ratio calculated for each sample. The lymphocytes derived from the patients with Huntington's chorea were found to be more susceptible to X irradiation than were the lymphocytes derived from controls. This was true both for whole blood and separated lymphocyte cultures. This susceptibility was found not to be the result of the main types of medication received by the patients. The small differences between viability ratios from patients and controls and the degree of overlap makes this test unsuitable for the prediction of asymptomatic carriers of the Huntington's chorea gene.